2003
DOI: 10.1039/b303024e
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field-induced growth and self-assembly of cobalt nanocrystallites

Abstract: The growth and assembly behavior of cobalt magnetic nanocrystallites under an external magnetic field were studied. Co polycrystalline wires with an average length of 2 mm and diameter of 13 mm were formed by the self-assembly of Co nanocrystallites (15 nm on average) under the induction of a 0.25 T external magnetic field. The wires were nearly parallel because their axes were all parallel to the magnetic line of force. The M s and H c values of the sample, 111 emu g 21 and 389 Oe, are higher than those of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
117
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 24 publications
(20 reference statements)
5
117
0
Order By: Relevance
“…Another advantage of this approach is that the reaction proceeds at atmospheric pressure. It is widely believed that magnetic fields may have an effect on the growth of magnetic materials, [20,21] and thus we have introduced a magnetic force into the reaction system. It has been found that the presence of an external magnetic field influences crystal growth to produce different morphologies such as nanospheres, nanowires, and nanoflowers.…”
mentioning
confidence: 99%
“…Another advantage of this approach is that the reaction proceeds at atmospheric pressure. It is widely believed that magnetic fields may have an effect on the growth of magnetic materials, [20,21] and thus we have introduced a magnetic force into the reaction system. It has been found that the presence of an external magnetic field influences crystal growth to produce different morphologies such as nanospheres, nanowires, and nanoflowers.…”
mentioning
confidence: 99%
“…Due to this reason the types of self-assembled nanostructures formed by spherical magnetic colloids are far richer than those which are driven by all-attractive, spherically symmetric potentials of van der Walls interactions. The dipolar attraction is the strongest if the dipoles are put ''in-line'' configuration, which promotes the nanomagnets to assemble into linear chains [82][83][84][85] or ring structures 86,87 from dilute solutions. The type of the morphology depends on the magnetic interaction energy in comparison to the thermal fluctuations.…”
mentioning
confidence: 99%
“…Each carbon material has a different way of aggregating upon cooling of these hexagonal layers, which leads to the formation of various textures. Recently, magnetic field-induced growth and self-assembly of cobalt nanocrystallites was studied by Niu et al [5]. Other reports in which a chemical reaction was conducted in a magnetic field include the order observed in assemblies of superparamagnetic carrier particles reported by Rotariu [6], strain detected in iron-based ferromagnetic shape memory alloys reported by Sakamoto et al [7] and superconductivity measured in hybrid ferromagnets [8].…”
mentioning
confidence: 96%